2018
DOI: 10.3892/mmr.2018.9004
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy by targeting of VGKC complex for seizure control and prevention of cognitive impairment in a mouse model of epilepsy

Abstract: Epilepsy is a type of refractory neurologic disorder mental disease, which is associated with cognitive impairments and memory dysfunction. However, the potential mechanisms of epilepsy are not well understood. Previous evidence has identified the voltage gated potassium channel complex (VGKC) as a target in various cohorts of patients with epilepsy. In the present study, the efficacy of an antibody against VGKC (anti-VGKC) for the treatment of epilepsy in mice was investigated. A mouse model of lithium-piloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…However, these crucial genes were not involved in KEGG pathway-related regulation. Previous research has shown that three of the four key potassium channel genes (KCNA1, KCNA2, KCNJ11, and KCNS1) play vital roles in seizures and epilepsy (8)(9)(10). Four key potassium channel genes Lines are used to mark the position of members from the gene set in the gene sorting list, and the black line represents that the genes from the sorting gene table exist in the functional annotation gene set of the current analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these crucial genes were not involved in KEGG pathway-related regulation. Previous research has shown that three of the four key potassium channel genes (KCNA1, KCNA2, KCNJ11, and KCNS1) play vital roles in seizures and epilepsy (8)(9)(10). Four key potassium channel genes Lines are used to mark the position of members from the gene set in the gene sorting list, and the black line represents that the genes from the sorting gene table exist in the functional annotation gene set of the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Potassium channels in cell membranes play a critical role in regulating neuronal excitability by controlling the transport of potassium ions across cells (4)(5)(6). Several potassium channels are associated with TLE, primarily based on animal experiments (7)(8)(9)(10). Research on the association between potassium levels and epilepsy may provide novel insights into the mechanisms and treatments of epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…The mice treated with VGKC antibodies had also inhibited motor seizures and hippocampal damage, compared with control mice. It is suggested that VGKC may even be a potential target for the treatment of epilepsy (171).…”
Section: Antibodies: Glyr Antibodiesmentioning
confidence: 99%